Purification and partial characterization of novel penicillin V acylase from Acinetobacter sp AP24 isolated from loktak lake, an indo-burma biodiversity hotspot - Philem, Pushparani Devi; Sonalkar, Vidya V.; Dharne, Mahesh S.; Prabhune, Asmita (Preparative Biochemistry & Biotechnology, 2016)
Members of the bacterial genus Acinetobacter have attracted great attention over the past few decades, on account of their various biotechnological applications and clinical implications. In this study, we are reporting the first experimental penicillin V acylase (PVA) activity from this genus. Penicillin acylases are pharmaceutically important enzymes widely used in the synthesis of semisynthetic beta-lactam antibiotics. The bacterium, identified as Acinetobacter sp. AP24, was isolated from the water of Loktak Lake (Manipur, India), an Indo-Burma biodiversity hotspot. PVA production was increased threefold in an optimized medium with 0.2% sodium glutamate and 1% glucose as nitrogen and carbon sources respectively, after 24hr of fermentation at 28 degrees C and pH 7.0 with shaking at 180rpm. The enzyme was purified to homogeneity by cation-exchange chromatography using SP-sepharose resin. The PVA is a homotetramer with subunit molecular mass of 34 kD. The enzyme was highly specific toward penicillin V with optimal hydrolytic activity at 40 degrees C and pH 7.5. The enzyme was stable from pH 5.0 to 9.0 at 25 degrees C for 2hr. The enzyme retained 75% activity after 1hr of incubation at 40 degrees C at pH 7.5.
Keywords: 6-APA; Acinetobacter; Loktak Lake; Penicillin V acylase